Edukasi Faktor-Faktor yang Mempengaruhi Kejadian ISPA pada Anak di Puskesmas Andalas Padang - Indah Kesuma, Sari; Mailita, Weni (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2024)
Upper Respiratory Tract Inspection (ARI) is a condition caused by a virus that often attacks children and adults. According to WHO (2018), around ± 13 million children under five in the world die and these deaths. ISPA is one of the main causes of death, killing ± 4 million out of ± 13 million children under five every year. Several risk factors consist of age, gender, nutritional status, toddler immunization status, low birth weight, exclusive breastfeeding, residential density, parental education, mother's knowledge, economic status, presence of smokers. The aim of this service is to improve the knowledge and technology of the community at the Andalas Padang Community Health Center regarding the impact of ISPA on public health. The methods used are interactive lectures, question and answer, and evaluation. The results of the outreach showed an increase in public knowledge and prevention regarding ARI diseases. There is a need for continuous counseling and outreach from the local health center regarding the health of the respiratory system. The aim of this community service is to increase parents' knowledge and attitudes towards ISPA incidents in the home and surrounding environment. This community service activity was carried out for one day by providing education. Providing education on the dangers of ISPA and its prevention